Glutamic acid derivatives as gelators for electrolyte of lithium ion batteries. Issue 91 (16th September 2016) - Li, Liping; Zhang, Qiuxia; Huo, Hong; Zhou, Jianjun; Li, Lin
Abstract : Organic gelators were synthesized to prepare gel electrolyte with wider electrochemical stable window. Abstract : Organic gelators of glutamic acid derivative were synthesized, which have been successfully used to gel commercial electrolyte for lithium ion battery. The organic gelators self-assembled to form 3D fibrillar structures with very high porosity in the electrolyte solvent. Thermal stability of the gel electrolyte increased with the length of side chain and concentration of gelators. When the side chain length of gelator was 22 carbons, the gel electrolyte could endure temperature higher than 60 °C with the addition 2 wt% gelator. The most prominent advantage of gel electrolyte over liquid electrolyte was that it could broaden the electrochemical stable window, which has potential application in high voltage lithium ion batteries. With the addition of organic gelator, conductivity of the gel electrolyte would decrease a little, but it still showed the conductivity–temperature behavior of liquid electrolyte. The cells with gel electrolyte showed similar cycling performance as those with liquid electrolyte, which indicated that the organic gelators of glutamic acid derivatives could be used in lithium ion batteries, especially in high voltage lithium ion batteries.